Pale, Soft and Exudative (PSE) and Dark, Firm and Dry (DFD) Meat Determination in Broiler Chicken Raised Under Tropical Climate Management Conditions - Freitas, Arlan S.; Carvalho, Leila M.; Soares, Adriana L.; S. Oliveira, Maria E. da; Madruga, Marta S.; S. Neto, Arnoud C. de; Carvalho, Rafael H.; Ida, Elza I.; Shimokomaki , Massami (International Journal of Poultry Science, 2017)
Background and Objective: The Brazilian poultry industry has difficulties in maintaining meat quality standard as the country presents diverse climate conditions particularly having tropical and subtropical zones. Whilst the total gross production is located within the subtropical zones no much is currently known in the tropical zone particularly within the North Eastern (NE) region. This study was conducted to evaluate the broiler breast meat quality by quantifying the incidence of pale, soft and exudative (PSE) and dark, firm and dry (DFD) meat in a commercial processing plant during the dry and rainy seasons in the Brazilian NE region. Materials and Methods: A total of 2,800 breast samples were collected during the dry (n = 1,400) and rainy (n = 1,400) season. The animals were slaughtered and carcass processed according to the standard industry practices. The student’s t-test with a 5% probability (p<0.05) was used to compare the differences among the averages of lightness (L*), redness (a*), yellowness (b*), ultimate pH (pHu) and Water Holding Capacity (WHC) in pectoralis major. Results: The incidence of PSE meat was 43.53 and 10.46% in dry and rainy season, respectively. Additionally, 3.3% of DFD meat was found as the result of wet weather conditions only observed in the rainy season. Conclusion: The high occurrence of PSE-meat suggested the need to control broiler pre and pos-slaughter handling conditions in order to maintain the meat quality. Despite of hot weather conditions either in the rainy or dry season, it is feasible to motivate the broiler growth activities within the Brazilian tropical zone.